Kepatuhan Wajib Pajak Usaha Mikro Kecil Menengah Di Jakarta Pada Awal Masa Pandemi Covid - Diana Frederica; Chrisnawati Novelia; Deni Iskandar (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2021)
The purpose of this study is to analyze taxpayer compliance on the implementation of PP. 23 of 2018 at the start of the covid pandemic. This type of research is descriptive qualitative research with a sample size of 20 MSME actors with a turnover of not more than Rp. 4.8 billion in one tax year. The results of the analysis conclude that MSME actors are greatly helped by the reduction in tax rates because they are in accordance with the scale of the UMKM. However, there are still MSMEs that have not fulfilled their tax obligations even though the tax rate has been lowered to 0.5% due to the decline in turnover due to the pandemic, which disrupts the cash flow of MSMEs. There are several inputs as an implication of this research, namely the need for tax socialization to MSME actors and training on the use of taxation applications so that it is better understood and tax relief.